CHILD STUNTING: REVEALING THE LACK OF CONCERN OF NATIONAL MEDIA IN INDONESIA - Suraya Mansur; Nurhayani Saragih; Afgiansyah Afgiansyah; Wiwik Novianti; S Bekti Istiyanto (Profetik: Jurnal Komunikasi, 2023)
Campaigns carried out by the Ministry of Health and other government collaborations will not be successful without mass media broadcasts. Hence a phenomenon occurs that there is still a lack of discussion regarding the media raises the issue of stunting in the media. Thus this study aims to find out how concerned the media is in news portals regarding child stunting issues in Indonesia. The theory which is used in this study is the theory of health communication and online reporting. This study uses a post-positivistic paradigm, a digital media content analysis method with a qualitative approach. The data collection technique captures big data regarding stunting news in the news portal during November 2022 on National Health Day. The results of the study show that the online news portal with high awareness is tribunnews.com around 528 news out of 750 news. The most widely published issue is the government's commitment to reduce the stunting rate in Indonesia and the government's campaign programs as evidence of a concrete movement to increase public awareness regarding the prevention and treatment of stunting in society. The benefits of this research are expected to further strengthen the insights of researchers both in terms of expertise and scientific competence of researchers.